Influence of prenatal exposition for selenium on visual evoked potentials (FVEP) in rats - Herba, Ewa; Pojda-Wilczek, Dorota; Plech, Agata; Pojda, Stefan; Szkilnik, Ryszard (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Selenium is an essential trace element in lower concentration and toxic in higher one. The aim of the study was to find out if the small doses of selenium taken by pregnant rats change the visual evoked potential ( FVEP) curve in newborns. The FVEP was done in 4-6 month old white, Wistar, offsprings rats. 8 rats were from the mothers which drank water solution of natrium selenosum in dose 1.5 ppm through the whole pregnant time ( selen group) and 8 rats were from the pure farm (control group). The shortened of the latencies and increased of the amplitudes of N1 and P1 waves were observed in the selenium exposed group in comparison to the control, but only the changes between amplitudes of N1 and P1 were statistically significant. The small doses of selenium by improving the VEP may probably change for the better vision too.